Slum upgrading in the era of World-Class city construction: the case of Lagos, Nigeria. Issue 2 (3rd May 2020) - Adama, Onyanta
ABSTRACT: The paper examines the tensions that accompany slum upgrading in the era of world-class city construction. The focus is a slum upgrading project in Lagos, Nigeria. The paper observes the intertwining of modernist and neoliberal ideologies in world-class city construction and in slum upgrading projects. The entanglement centres on a number of shared interests; the prioritization of infrastructure and notions about urban space, participation and citizenship. As documented, the project and by extension world-class city construction fails to acknowledge the livelihoods of the poor and is undermined by protests. Historical legacies and systemic failings of governance present additional obstacles. The paper seeks to broaden the scope of world-class city research by acknowledging the local context, but at the same time recognizing the global links. Along these lines, the paper suggests that slum upgrading provides an opportunity to examine how the local is inserted into the global.